Supply Chain Management Values for the Society In A Community-Based Tourism Village - Suranto, Suranto; Nilamsari, Dwi; Eko Soetjipto, Budi; Aji Fitriani, Sofa (ExcelingTech, 2020)
This research aims to describe the values of supply chain management that develop in a tourism village that is managed through the community-based tourism (CBT) model. This is qualitative research with ethnographic design. The data of the present research were collected through in-depth interviews, observation, and documentation. The resource persons of the research were tourism village managers and traders in Papringan Market, Temanggung, Central Java, Indonesia. To ensure the trustworthiness of the research data, source triangulation analysis and participant observation were performed. Several steps were involved in data analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that the values of supply chain management found in Papringan Market traders included: (1) Self-knowledge, the traders already knew about the business and carried out their own production and marketing processes, (2) Search skills, the traders could easily get raw materials for their business and implemented an effective marketing system to attract customers, (3) Computation skills, traders prepared themselves with the risks that would come. They did not only focus on sales in the Papringan Market but also have other jobs, 4) Practical knowledge, the traders had understood enough to make innovations in their business, but the changes were not significant, 5) Communication skills, communication between sellers and consumers in the Papringan Market was well-established and conducive, even among fellow traders and market managers, 6) Imagination, traders had insufficient idea and imagination to develop their products because they still relied on market demand, 7) Foresight, traders still followed the flow of the Papringan Market and did not yet have thoughts or idea for their products in the future.